Development of an empirical correlation to predict the effectiveness of heat and mass transfer from textiles in a rotating drum - Mahmoud Rasti; Mehdi Rasti; Ji Hwan Jeong (Case Studies in Thermal Engineering, 2024)
The clothes dryer is one of the most energy-consuming household appliances. Modeling the rotating drum within clothes dryers presents significant challenges due to the concurrent heat and mass transfer between the air and textiles, exacerbated by the random motion of textiles within the drum. To address the intricacies of drum modeling, many researchers have traditionally assumed a constant value for the area-mass transfer coefficient, neglecting its dependence on operational parameters. This study proposes a novel dimensionless correlation for predicting the moisture evaporation rate, based on the concept of heat and mass transfer effectiveness. To develop the correlation, we conducted an extensive series of 36 experiments, taking into account various factors such as textile type, textile size, textile mass, drum size, rotational speed of the drum, air temperature, relative humidity, airflow rate, and moisture content. The new correlation with previous ones were compared using ten sets of independent experimental data. The average absolute deviation of the present correlation was found to be 11.63 %, while Gluesenkamp et al.'s correlation exhibited a deviation of 5970.8 %, and Novak et al.'s correlation showed a deviation of 62.90 %. Newly proposed correlation demonstrates superior agreement with the independent data sets when compared to other empirical correlations.